Analyzing Airline Services and Communication Systems by Designing Machine Learning Model to Predict Passenger Satisfaction - Iskandar, Rodzan; Anies, Okta Reni Azrina Rasyid; Iskandar, Rusydi; Kesuma, Mezan el-Khaeri; Konecki, Mario (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
This research explores the methods of assessing airline passenger satisfaction through surveys and analyzing factors that are strongly linked to whether a passenger is satisfied or dissatisfied. The aim is also to investigate if it is possible to predict passenger satisfaction levels. The dataset used in this study comes from a Kaggle dataset titled